Effect of Dietary Pumpkin Stem Waste on Haematological Indices, Meat and Serum Lipid Profiles of Rabbits - J. S. Ekpo; N. J. Okeudo; M. C. Uchegbu; E. B. Etuk (European Scientific Journal, ESJ, 2019)
This study evaluated the effect of different supplementary dietary levels of pumpkin stem waste (PSW) on the haematological indices, meat and serum lipid profile of rabbits. Three experimental feed regime:D1 (control), basal feed+ 0% PSW; D2,basal feed + 5% PSW and D3, basal feed + 10% PSW were randomly assigned to the three treatment groups in a 3x2 factorial arrangement in a completely randomized design experiment. The PSW percentage were offered on rabbit weight basis. Thirty six (18 males and 18 females) crossbred (California x New Zealand white) weaned rabbits aged 6 and 7 weeks were divided into three treatment groups of 12 rabbits each with 4 rabbits per replicate (2 females and 2 males) and randomly allotted to the three dietary treatments. At the end of 12 weeks feeding trial( prior to slaughtering), blood samples were collected from 6 rabbits (3 males and 3 females) per treatment totalling 18 rabbits and used to determine the serum lipid profile and haematological blood indices. Similarly, breast meat sample was used to determined lipid profile. Results obtained showed that while red blood cell (RBC),haemoglobin (Hb), packed cell volume (PCV),Mean cell haemoglobin (MCH) and mean cell haemoglobin concentration MCHC increased (P<0.05) with increasing dietary PSW. White blood cell (WBC) and MCHC however showed no significant difference (P>0.05) among the treatments groups. Lipid profile of both serum and meat indicated that HDL increased significantly (P<0.05) with increase in PSW while total cholesterol (TC), low density lipoprotein (LDL), triglyceride (TG) and very low density lipoprotein (VLDL) decreased significantly (P<0.05). Diet by sex interaction showed that male rabbits recorded significantly different (P<0.05) values from their female counterparts in all the blood and meat lipid parameters assessed. These results suggest that pumpkin stem waste is hypolipidaemic therefore could lower rabbits’ meat cholesterol and improve blood constituents.